Hormone therapy and urine protein excretion: a multiracial cohort study, systematic review, and meta-analysis - Kattah, Andrea G; Suarez, Maria L G; Milic, Natasa; Kantarci, Kejal; Zeydan, Burcu; Mosley, Thomas; Turner, Stephen T; Ware, Erin B; Kardia, Sharon L R; Garovic, Vesna D (Menopause (New York, N.Y.), 2018)
Experimental models suggest estrogen has a renoprotective effect, but human studies show variable results. Our objective was to study the association of hormone therapy (HT) and albuminuria in postmenopausal women and to synthesize the results with outcomes from prior studies. We analyzed data from postmenopausal women who participated in the second study visit (2000-2004) of the Genetic Epidemiology Network of Arteriopathy (GENOA) study. The exposure was self-reported HT use and the outcome was albuminuria (urine albumin-to-creatinine ratio >25 mg/g creatinine). We also conducted a systematic review and meta-analysis on the association of HT and urine protein in postmenopausal women. Continuous and dichotomous measures of protein excretion were converted to a standardized mean difference (SMD) for each study. In the GENOA cohort (n = 2,217), there were fewer women with albuminuria among HT users than nonusers (9% vs 19%, P < 0.001). HT use was associated with decreased odds of albuminuria (odds ratio 0.65, 95% confidence interval (CI), 0.45-0.95), after adjusting for significant differences in age, race, education, comorbidities, and the age at and cause of menopause. The SMD of the effect of HT on urine proteinuria/albuminuria in the randomized control trials (n = 3) was 0.02 (95% CI, -0.29 to 0.33) and -0.13 (95% CI, -0.31 to 0.05) in the observational studies (n = 9). There was significantly less albuminuria among HT users (SMD -0.15, 95% CI, -0.27 to -0.04) in the 9 studies that only reported albuminuria as an outcome and in the 10 studies with a comparator arm (SMD -0.15, 95% CI, -0.26 to -0.04). HT is associated with decreased odds of albuminuria, but some of the observed benefits may be related to reported outcomes, the presence of a comparator arm, and the type of study design.